(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This review article focused on anxiety therapy, and its primary objective was to shed light on the possible therapeutic efficacy of the active components investigated in the initial preclinical study. It also encourages the discovery of new antianxiety medications derived from plants. Potential screening of the preclinical research on phytoconstituents' antianxiety effects are also highlighted (in-vitro, in-vivo). PubMed, Clinicaltrials.gov, The Plant List (TPL, www.plantlist.org), and Science Direct were used to learn about the pharmacology of phytoconstituents, the historical applications of medicinal plants for anxiety, and the status of phytoconstituents in clinical inquiry. Search results were supplied that used a specific syntax and were restricted to articles that fulfilled particular parameters. Traditional uses of this medicinal plant include relief from anxiety, which makes sense given that seventy percent or more of the phytoconstituents investigated here functioned predominantly on the GABAergic system. Linalool and hypericin are the two phytoconstituents studied for potential clinical benefit in anxiety. Support for the discovery and development of novel antianxiety drugs derived from medicinal plants comes from both preclinical and clinical research on the phytoconstituents used to treat anxiety and its associated comorbidities. A deeper understanding of the pharmacodynamic and pharmacokinetic picture of phytoconstituents is required to assess their efficacy and safety; additional randomized and controlled clinical trials are required. There should be an assessment of botanical assets as well.